RECONSTRUCTION OF STATE-OWNED ENTERPRISE LEGAL REGULATIONS FROM A GOOD CORPORATE GOVERNANCE PERSPECTIVE: NORMATIVE ANALYSIS OF ESTABLISHMENT, OWNERSHIP, AND INSTITUTIONAL TRANSFORMATION BASED ON THE LATEST REGULATIONS FOLLOWING THE JOB CREATION LAW - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This study provides a normative analysis of the reconstruction of the legal regulation of State-Owned Enterprises (SOEs) from the perspective of Good Corporate Governance (GCG) after the Job Creation Law, focusing on the establishment of new SOEs through a feasibility study of the SOE Supervisory Board, the ownership of dual-class A and B shares by BPI Danantara, and institutional transformation via super holding companies and the Business Judgment Rule as stipulated in Law No. 1/2025 and Law No. 16/2025, which revolutionise the separation of regulatory and operational functions for transparency, independence, and efficiency. The results of the analysis show the alignment of regulations with GCG principles, although disparities still require harmonisation through independent committees and digital reporting, with positive implications for the global competitiveness of SOEs through strategic holding synergies and optimisation of state budget dividends. The study recommends strengthening criminal sanctions for ESG transformation and integration for sustainable governance, serving as a reference for SOE policy-making. regulations.